Quality and Conservation of Riparian Forest in a Mountain Subtropical Basin of Argentina - Fernandez, Romina Daiana (2016)
The aims of this work were to describe the conservation status of riparian forests located in a mountain subtropical basin of Tucumán province, Argentina, and assess how the quality of riparian forests is related with altitude, plant species richness, proportion of exotic species, and Total Suspended Solids (TSS) in adjacent rivers. Composition and species richness of riparian forests were studied at 16 sites located along an altitudinal gradient and TSS was determined from water samples collected in each site. In order to evaluate conservation status of riparian forests, we calculated an index of Quality of Yungas Riparian Forests (QBRy). We recorded 90 plant species at all sites, from which 77% were native. QBRy index was mainly associated with altitude and varied from riparian forests with good preservation or slightly disturbed to those with extreme degradation. At lower altitude, forests were more disturbed, more invaded by exotic plant species, and closer to urban and cropped areas. QBRy was not correlated with species richness or TSS. Like other riparian forests of Argentina, plant species invasion increased their degradation; therefore, future studies should focus on native riparian forests conservation and on the management of invasive plant species, which affect their quality.